SYSTEMATIC LITERATURE REVIEW: KAJIAN PROBLEM BASED LEARNING BERBASIS DEMONSTRASI PADA JENJANG SEKOLAH MENENGAH PERTAMA - Sari, Sindi Purnama; Adha, Idul; Refianti, Rani (JOURNAL of MATHEMATICS SCIENCE and EDUCATION, 2024)
This study aims to examine the concept and application of the demonstration-based Problem Based Learning (PBL) Model in junior high school mathematics learning. The articles used as a source of review are 9 articles that have been published in accredited national journals. From the results of the review, findings were obtained. This research uses the Systematic Literature Review (SRL) method, which is carried out through the stages of identifying, reviewing, exploring, and interpreting all reference articles that have been collected. Based on the literature review that has been conducted, it shows the relevance of the demonstration-based Problem Based Learning (PBL) model in an effort to improve student learning skills